Sequencing and analysis of chromosome 1 of Eimeria tenella reveals a unique segmental organization. - Ling , King Hwa; Rajandream, Marie Adèle; Rivailler, Pierre; Ivens, Alasdair C.; Yap, Soon J.; Madeira, Alda Maria Backx Noronha; Mungall, Karen L.; Billington, Karen J.; Yee, Wai Y.; Bankier, Alan T.; Carroll, Fionnadh; Durham, Alan Mitchell; et al. (Cold Spring Harbor Laboratory Press, 2007)

(untitled)
Eimeria tenella is an intracellular protozoan parasite that infects the intestinal tracts of domestic fowl and causes coccidiosis, a serious and sometimes lethal enteritis. Eimeria falls in the same phylum (Apicomplexa) as several human and animal parasites such as Cryptosporidium, Toxoplasma, and the malaria parasite, Plasmodium. Here we report the sequencing and analysis of the first chromosome of E. tenella, a chromosome believed to carry loci associated with drug resistance and known to differ between virulent and attenuated strains of the parasite. The chromosome - which appears to be representative of the genome - is gene-dense and rich in simple-sequence repeats, many of which appear to give rise to repetitive amino acid tracts in the predicted proteins. Most striking is the segmentation of the chromosome into repeat-rich regions peppered with transposon-like elements and telomere-like repeats, alternating with repeat-free regions. Predicted genes differ in character between the two types of segment, and the repeat-rich regions appear to be associated with strain-to-strain variation.